Ossifying chondrolipoma of the tongue - Tasić Desanka; Pavlović Milorad; Stanković Dragan; Dimov Irena; Stanojević Goran; Dimov Dragan (Vojnosanitetski Pregled)
Introduction. Chondrolipomas and osteolipomas are uncommon variants of lipomatous tumors. Case report. We presented a 60-year-old woman with ossifying chondrolipoma of the tongue. Clinical examination revealed a firm nodular mass, located in the midline of the posterior region on the dorsal surface of the tongue. Histologically, the lesion was well-delimited showing areas of mature adipocytes arranged in lobules and separated by fibrous connective tissue septa, islands of mature cartilaginous tissue and osseous metaplasia. Trabeculae of lamellar bone within a fibro-fatty background were visible throughout the tumor. The cartilaginous areas merging centrally with bone formation and fatty marrow tissue were present, as well as the hematopoietic elements in the fatty marrow. The bone forming was found to be through both membranous and enchondral mechanisms. Conclusion. Ossifying chrondrolipoma with hematopoietic elements is extremely unusual lesion. This interesting entity should be kept in mind in the differential diagnosis of lingual lesions.